Effects of COVID-19 lockdown on a bariatric surgery waiting list cohort and its influence in surgical risk perception - Beisani, Marc (Langenbecks Arch Surg, 2020)
PURPOSE: The COVID-19 outbreak has forced a 2-month lockdown (LD) in Spain. We aimed to assess how that had affected our cohort of bariatric patients waiting for surgery. METHODS: A review of electronic records and a structured phone interview with each patient were conducted. Changes in severity of obesity were analyzed using the Obesity Surgery Score (OSS) and changes in health-related quality of life (HRQoL) using the validated EQ-5D questionnaire. Other miscellaneous questions about behavior modifications and surgical risk perception were also analyzed. RESULTS: All 51 patients fully answered the questionnaires. Mean age was 47 years and mean time on waiting list 91 days. Mean BMI increased during LD (42.7 vs 43.2; p < 0.001). Both OSS (2.84 vs 3; p = 0.011) and EQ-5D (69 vs 64; p < 0.001) mildly worsened during LD, mainly due to psychosocial issues. Twenty-seven patients (53%) thought that perioperative risks were higher under the current circumstances but they were as willing to undergo surgery as those who believed that the risks had not increased (74% vs 87%, p = 0.2). CONCLUSIONS: COVID-19 LD had a significant but mild effect on our cohort of bariatric surgery waiting list patients. Although perioperative risk perception had increased, patients were still willing to undergo their planned surgeries.